2015
DOI: 10.6007/ijarbss/v5-i9/1816
|View full text |Cite
|
Sign up to set email alerts
|

Gastronomy Tourism as an Alternative Tourism: An Assessment on the Gastronomy Tourism Potential of Turkey

Abstract: Gastronomy tourism, besides being the most important means of economic development, it is also the most significant part of the fastly developing cultural tourism market. Many recent researches emphasized that the culinary culture of a target destination has a significant part in the travel experience. Travelling for the purpose of experiencing the new and unbelievable food, wine and other inimitable local gastronomy assets of another region is gastronomy tourism. In Turkey, tourism policies had been limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…This implies that gastronomy tourists travelling to Ilocos Region share the importance of Ilocanos authentic local cuisine to other tourists through word of mouth. This is very much reflected on the paper of Sahin (2015) stating that gastronomy tourism is a type of tourism that appeals to high income and intellectual tourists, aged between 35 and 55, who want to visit destinations of different food cultures, who are open to new experiences such as food, to share their experiences with others and spend much. In the marketing of destinations, the gastronomy tourism creates important power with its potential for year-round performance, increases in spending and staying time over other types of tourism, contributes to local development, environmentally sensitive development, authentic and inimitable product range exclusively in this region.…”
Section: Factors Affecting the Attractiveness Of Gastronomic Products In Terms Of Adding Value To The Authenticitymentioning
confidence: 99%
“…This implies that gastronomy tourists travelling to Ilocos Region share the importance of Ilocanos authentic local cuisine to other tourists through word of mouth. This is very much reflected on the paper of Sahin (2015) stating that gastronomy tourism is a type of tourism that appeals to high income and intellectual tourists, aged between 35 and 55, who want to visit destinations of different food cultures, who are open to new experiences such as food, to share their experiences with others and spend much. In the marketing of destinations, the gastronomy tourism creates important power with its potential for year-round performance, increases in spending and staying time over other types of tourism, contributes to local development, environmentally sensitive development, authentic and inimitable product range exclusively in this region.…”
Section: Factors Affecting the Attractiveness Of Gastronomic Products In Terms Of Adding Value To The Authenticitymentioning
confidence: 99%
“…Turkish cuisine is regarded as one of the oldest and best cuisines (Akgöl, 2012). This is because of the geographic location of Turkey and its historical foundations that has strongly contributed to form a Turkish cuisine culture, which has created a great diversity in its cuisine (Sahin, 2015).…”
Section: Gastronomy Tourismmentioning
confidence: 99%
“…It has become famous for its dishes such as kebabs. Recent studies have shown that the taste and diversity of Turkish cuisine is a major factor in attracting foreign tourists who regard Turkish cuisine as rich, attractive and delicious (Sahin, 2015). Turkish cuisine is regarded as one of the oldest and best cuisines (Akgöl, 2012).…”
Section: Gastronomy Tourismmentioning
confidence: 99%
“…This is resulting in an increasing number of tourist destinations becoming very sought after because of their unique culinary and gastronomy (Hjalager, 2002). For example, Sahin (2015) discussed the growth in gastronomy tourism as an alternative tourism field in Turkey. He stated that gastronomy tourism helps support the development of rural areas that consists of seven regions that have different climates and vegetation.…”
Section: Gastronomy Tourism In Rural Settingsmentioning
confidence: 99%